2022
DOI: 10.1192/j.eurpsy.2022.31
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and related factors of child posttraumatic stress disorder during COVID-19 pandemic: A systematic review and meta-analysis

Abstract: This peer-reviewed article has been accepted for publication but not yet copyedited or typeset, and so may be subject to change during the production process. The article is considered published and may be cited using its DOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…The estimated prevalence in China was significantly lower than in Italy, Germany, and America. Consistent with the existing studies, a meta-analysis found that the prevalence of child posttraumatic stress disorder in China was significantly lower than the Italian and American estimates [ 74 ]. Firstly, the difference may be due to epidemic crisis degrees and prevention and control policies in different countries.…”
Section: Discussionsupporting
confidence: 71%
“…The estimated prevalence in China was significantly lower than in Italy, Germany, and America. Consistent with the existing studies, a meta-analysis found that the prevalence of child posttraumatic stress disorder in China was significantly lower than the Italian and American estimates [ 74 ]. Firstly, the difference may be due to epidemic crisis degrees and prevention and control policies in different countries.…”
Section: Discussionsupporting
confidence: 71%
“…High heterogeneity was found [ 52 , 63 , 93 , 95 , 122 ] and subgroup analyses showed higher prevalence rates of depression and anxiety symptoms in studies with a higher proportion of girls/females and in adolescents compared to children. PTSD symptom prevalence rate was higher in children and adolescents from Northern America and Europe compared to Southeast Asia [ 52 , 63 , 93 , 137 ]. In only few reviews with meta-analyses, a pooled prevalence rate in caregivers (e.g., mothers of young children [ 126 ]) and in working populations (e.g., teachers [ 58 , 108 ]) was calculated (Tables A, B, and C in S2 Text ).…”
Section: Resultsmentioning
confidence: 99%
“…Additional file 12 [ 54 , 67 , 77 , 139 , 153 ] summarizes single-arm evidence about events caused by the COVID-19 vaccine. Additional file 13 [ 49 , 50 , 58 , 82 , 99 , 113 , 142 ] summarizes single-arm evidence about health impacts during the pandemic.…”
Section: Resultsmentioning
confidence: 99%